Reutilização da água recuperada da quebra da emulsão de fluido de corte degradado proveniente de indústria metal-mecânica - Gonçalves, Paulo Cézar (2019)
The manufacturing industry is of fundamental importance for the Brazilian economy, in order to maintain its competitiveness with the international market, it is necessary to constantly seek improvements in processes, optimizing its manufacturing tools, having as vision the excellence in product quality. In it’s turn, the cutting fluid is part of this process, as it contributes to the fact that the machining is an increasingly faster process and at the same time maintains the quality in the products manufactured. After the life of the cutting fluid, it is necessary to dispose of it properly so as not to contaminate the environment. On the other hand, we are looking for methods that can make the reutilization of part of this product, which contains, in its composition, approximately 90% of water. In this sense, the work sought the optimization of the breaking of emulsion of cutting fluid using the cations Calcium (Ca2+) and Magnesium (Mg2+) and pH control. As auxiliary tools of this research, we used the Rotational Central Compound Design (DCCR) planning method and as reading response variables in a UV scan spectrophotometer. After optimizing the parameters, the fluid emulsion breaking model validation was performed. Two new shear emulsions were formulated using water obtained from the emulsion breaking and a third control, these fluids were tested using Reichert Test type wear test, comparing them. The results presented after analysis of the tests indicate that it is possible to break the degraded cutting fluid emulsion using 0.02 (g) Ca (NO3)2 and 0.04 (g) Mg (NO3)2 as the minimum amount and 0.12 (g) of Ca (NO3)2 and 0.21 (g) of Mg (NO3)2 as the maximum amount, at pH 12.5 for both and allowing the aqueous phase of these results to be used to stabilize a new emulsion of cutting fluid. The Reichert Test, which performs the friction of the tool with the test body, allowed the collection of information such as the temperature in the region of the test body and the cutting fluid, thus making a comparison between the analyzed fluids. The collected responses indicate that of the three fluids tested, all presented the same pattern, both in the temperature of the cutting fluid and in the body of evidence. Another information collected and analyzed was the roughness, measured in the craters of the specimens, in the region that suffered the wear, and these data also presented similarities of results, leading to the conclusion that, the cutting fluids with 100% reuse water did not lose cooling capacity and lubrication, in front of the cutting fluid with public water supply.